Economic profitability and efficiency of honey production from the Asian honeybee (Apis cerana) in the mid-hills of Nepal - Anup Paudel; Narayan Prasad Tiwari; Suryamani Dhungana; Logan L. Britton (Journal of Agriculture and Food Research, 2025)
Beekeeping is a prominent industry in the Myagdi district of Nepal, with significant potential for commercial expansion through modern practices. Access to regional productivity and profitability information is pivotal for adopting new technologies and modern practices in beekeeping. This study evaluates the profitability and efficiency of honey production in the region, emphasizing the role of modern beekeeping techniques. The farm-level data of 110 beekeepers were collected across Beni Municipality and Mangala Rural Municipality. Profitability was assessed using the benefit-cost ratio (BCR), gross margin, and net margin, while efficiency was measured through the Cobb-Douglas production function and the Stochastic Frontier approach. Results revealed an average BCR of 1.67, with modern practices outperforming traditional methods. Resource efficiency analysis indicated underutilization of labor (60 %), artificial feed (27 %), and pasture management costs (86 %), suggesting opportunities for optimization. The mean technical efficiency of beekeeping enterprises was estimated at 0.81, indicating that improved management practices could increase output by approximately 19 % using the current level of inputs. This research highlights the need for targeted policies to enhance resource allocation, training programs, and access to modern beekeeping technologies. By addressing these gaps, the beekeeping sector in Myagdi can achieve greater efficiency and profitability, contributing to sustainable agricultural development in Nepal.